ChemInform Abstract: Magnetic Properties, Water Proton Relaxivities, and in‐vivo MR Images of Paramagnetic Nanoparticles. Issue 34 (4th August 2016) - Lee, Gang Ho; Chang, Yongmin
Abstract: Review: emphasis on Ln2O3‐based MRI contrast agwents; 40 refs.